INFLUENCE OF LARGE ARTIFICIAL POROSITY ON BENDING BEHAVIOUR OF TI6AL4V ELI ADDITIVELY MANUFACTURED SPECIMENS SUBJECTED TO TYPICAL LOADS DURING MASTICATION - Wessels, Adriaan; du Plessis, Anton; Yadroitsava, Ina; Els, Johan; Yadroitsev, Igor (The South African Journal of Industrial Engineering, 2020)
Effective quality control of implants made using additive manufacturing is an important task for suppliers to comply fully with existing regulations and certifications. To study the influence of porosity on the mechanical behaviour of mandibular implants produced by additive manufacturing, preliminary tests with longitudinal flat samples were performed with 3D point bending tests. Ti6Al4V Extra Low Interstitial (ELI) specimens with artificial porosity were designed and subjected to typical loads during mastication. In this work, a finite element simulation was constructed to investigate the bending behaviour of samples, which was consistent with the experimental results. The work shows that even large artificial cavities (designed up to 0.42 mm) do not significantly affect the strength of additively manufactured 2.5 mm-thick Ti6Al4V ELI specimens under typical static loads of mandibular implants, in the considered loading conditions, and for samples subjected to appropriate surface finishing and annealing heat treatment.